Long-term safety of glycopyrrolate/eFlow® CS in moderate-to-very-severe COPD: Results from the Glycopyrrolate for Obstructive Lung Disease via Electronic Nebulizer (GOLDEN) 5 randomized study - Ferguson, Gary T.; Goodin, Thomas; Tosiello, Robert; Wheeler, Alistair; Kerwin, Edward (Respiratory medicine, 2017)
The use of long-acting bronchodilators is an essential component of the management of chronic obstructive pulmonary disease (COPD). The GOLDEN 5 Phase III, randomized, active-controlled, open-label study was conducted to evaluate the long-term safety and tolerability of a nebulized glycopyrrolate formulation (SUN-101) delivered via the investigational eFlow® Closed System (eFlow® CS) nebulizer in subjects with moderate-to-very-severe COPD. Subjects were randomized in a 4:3 ratio to nebulized glycopyrrolate 50 μg twice daily (BID) or tiotropium 18 μg once daily (OD) and treated for 48 weeks. Subjects represented the general COPD population with real-world characteristics including severe disease, presence of comorbidities, and receiving background COPD therapy. Primary endpoints were the incidence of treatment-emergent adverse events (TEAEs), serious TEAEs, and discontinuations due to TEAEs. Secondary endpoints included the number of subjects with major adverse cardiovascular events (MACE); change from baseline in trough forced expiratory volume in 1 s (FEV1), and assessment of patient-reported outcomes. 1086 subjects received at least one dose of study drug. The overall incidence of TEAEs was comparable for subjects treated with glycopyrrolate (69.4%) or tiotropium (67.0%). Serious TEAEs occurred at similar rates in both treatment groups (glycopyrrolate, 12.3%; tiotropium, 10.5%). The most frequent TEAEs were COPD exacerbation/worsening and cough. Discontinuation due to TEAEs was higher in the glycopyrrolate group (10.0%) than the tiotropium group (2.8%) and related, in part, to the open-label study design, prior use of long-acting muscarinic antagonists and aerosol–airway interactions. Fewer subjects in the glycopyrrolate group experienced MACE (glycopyrrolate, n = 3 [0.5%]; tiotropium, n = 8 [1.7%]). Nebulized glycopyrrolate treatment resulted in improvements in trough FEV1 that were maintained over 48 weeks. Patient-reported health outcomes showed improvements, supporting the increases in trough FEV1. Treatment with nebulized glycopyrrolate was well tolerated over 48 weeks with the most common adverse events being COPD worsening and cough. The overall and cardiac safety and tolerability profile and improvements in pulmonary function and patient-reported health outcomes support the use of nebulized glycopyrrolate as a maintenance treatment for moderate-to-very-severe COPD. NCT02276222. •A randomized, open-label, Phase III, 48-week study evaluated the long-term safety and efficacy of nebulized glycopyrrolate.•Subjects with moderate-to-very-severe COPD were randomized to glycopyrrolate 50 μg BID or tiotropium 18 μg OD.•Nebulized glycopyrrolate was well-tolerated with an acceptable overall and cardiovascular safety profile.•Clinically important improvements in pulmonary function and patient-reported outcomes were observed over 48 weeks.